Fifteen years of the cologne medical model study course: has the expectation of increasing student interest in general practice specialization been fulfilled? - Zims, Heike (GMS J Med Educ, 2019)
Background: The 2002 Medical Licensure Act gave German universities certain freedoms for reforming their medical degree courses. The Medical Faculty of the University of Cologne took advantage of this opportunity and introduced a model study course in the winter semester 2003/04 through §41 of the Medical Licensure Act. One of the main reasons for this was that back then there was an increasing shortage of doctors in clinical curative medicine and GP primary care. This study investigates whether the introduction of the Cologne Model Study Course (MSG) can show stronger interest in curative medical work (especially General Practice) compared to students of the standard degree course (RSG). Methodology: The proof of added value was examined through graduate surveys conducted at the University of Cologne and through the proportion of students who completed the PY elective rotation “General Practice”. The students of the standard degree course (start of studies prior to winter semester 2003/2004) were compared with students of the model study course (start of studies from winter semester 2003/04 onwards). Measurements were carried out using descriptive frequency tables and correlation analyzes according to Spearman. Results: The students’ interest in curative medicine was already high (91%) even before the model study course was introduced and increased only slightly (to 91.9%). There is also only a slight increase in specialization in General Practice (RSG=5.9% vs. MSG=9.2%). However, selection of rotations in General Practice was significantly increased (RSG=1.9% vs. MSG=3.4%, r=0.046 **, p<0.005). Conclusion: The Cologne Model Study Course in Human Medicine has increased awareness of the subject of General Practice among students through a large number of curricular changes. The fact that only marginal effects can be demonstrated shows once more the strong dependence of choosing General Medicine as a career path on other factors (such as gender or the presence of positive role models) and emphasizes the necessity of promoting General Practice student education not only through increased curricular mapping but by additional innovative concepts to maximize the status of General Practice from the perspective of students.